Palladium-Catalyzed Cross-Coupling Reactions of Arylsiloxanes with Aryl Halides: Application to Solid-Supported Organic Synthesis - Traficante, Carla Inés (2014)
The solid-phase version of the Pd-catalyzed Hiyama reaction between a variety of aryltriethoxysilanes and immobilized aryl halides was developed. Smooth crosscoupling was achieved to afford the corresponding biaryl products in moderate to excellent yields. The described protocol would be particularly useful for the construction of 4′-substituted 1,1′-biphenyl derivatives